Juicy June: a mass-participation snack-swap challenge—results from a mixed methods feasibility study - Dorota Juszczyk (Pilot and Feasibility Studies, 2018)
Abstract Background Improving diet as a means of reducing the development of disease states and obesity is a public health priority. Although a growing number of countries have adopted policies to improve dietary patterns at the population level, as yet there are no established means of successfully bringing about change, suggesting that new approaches are needed. This study aimed to investigate the feasibility and proof of concept of a theoretically informed healthy eating intervention based on the model of successful month-long alcohol reduction or stop smoking campaigns (i.e. a mass-participation ‘challenge’ format). Methods The study was a mixed methods feasibility trial and proof of concept of an online intervention. Adults were recruited to take part in a month-long ‘Juicy June’ challenge in which they nominated one unhealthy daily snack and committed to replace this with fruit or vegetables. Behaviour change techniques to promote motivation, increase self-efficacy, promote social support, self-regulation and habit formation were integrated into materials provided off- and online to support dietary change. A Facebook group was used to provide information, encouragement and foster social support. Diet quality was assessed before and after the intervention. Reasons for taking part, adherence to the snack swap, use of the intervention materials and experience of taking part were explored using quantitative and qualitative measures. Results Ninety-one adults of whom 42% were either overweight or obese took part. Over the 4-week intervention period, participants consumed their intended fruit/vegetable snack on average 5 days/week; however, they still consumed their target unhealthy snack on average 2 days/week. Adherence to the snack swap was stable over the 4-week intervention period. The use of specific behaviour change tools (e.g. self-monitoring) was low. Sixty-seven percent of participants accessed the online Facebook forum, but there were no user-generated posts or content. Conclusions The study demonstrated that the concept of a novel snack swap mass participation campaign is acceptable and feasible. Further piloting to explore how to promote greater engagement with men and ethnic minority groups and how to promote social support and maximise engagement with behaviour change techniques would be valuable.